Working Under Pressure : Improving Labor Productivity through Financial Innovation - Carranza, Eliana; Donald, Aletheia; Grosset, Florian; Kaur, Supreet (World Bank, Washington, DC, 2018)
In developing countries, financial transfers within social and kin networks are ubiquitous and frequent. Though these transfers have social benefits, pressure to redistribute income can introduce a disincentive to work by reducing the payoff of exerting effort. This comes at a potential cost for the overall efficiency of the economy. The authors developed a financial innovation to study the impact of this redistributive pressure on workers’ labor supply and productivity. This innovation, a direct-deposit commitment savings account, enabled workers to convert productivity increases into private savings which cannot be accessed by others. In the first phase of their project, workers offered the direct-deposit commitment savings account increased their labor productivity and earnings by ten percent, which translates into an eighteen percent increase for workers who opened an account. The effect appears to be driven by workers increasing effort while on the job. Preliminary results show that the visibility of an account to one’s social network and the degree of redistributive pressure a worker faces are strong determinants of account take-up. This suggests that tackling the underlying cause for redistributive norms, the lack of consumption smoothing mechanisms, could improve output and growth in developing countries by addressing the root cause of the high demand for commitment savings products.